Characterization of carbon nanotubes prepared from palm oil by aerosol-assisted catalytic CVD method / Maryam Mohammad - Mohammad, Maryam (2015)
In this work, raman spectroscopy study was done on synthesized carbon nanotubes from palm oil by aerosol-assisted catalytic Chemical Vapor Deposition (CVD) method. The CNTs were prepared using aerosol-assisted single furnace and double furnace CVD and single furnace thermal CVD method. Palm Oil as a fixed parameter was used as the carbon precursor. Two types of catalyst were used that is Zinc Nitrate,Zn (NO3 )2 .1 ^ 2 0 + HMTA solution and Ferrocene, Fe powder. The carrier gas used for these experiments was Nitrogen gas. The synthesis parameter that has been studied were the effect of catalyst, difference in methods of preparing CNTs and effect of deposition temperature. Characterization techniques were done to produce high quality and smaller diameter of carbon nanotubes. The different structures of carbon nanotubes produced by different methods were characterized mainly by micro-Raman to identify carbon nanotubes from the characteristic spectral patterns and to determine quantitatively the amount of carbon nanotubes in a sample. These results were then supported by other type of characterization namely FESEM, and EDX to study the surface morphology of samples as well as determine the size diameter of carbon nanotubes and the percentage of composition of samples. Finally, TGA analysis was also done to calculate the amount of impurities (catalyst particles) left in the samples compared to the amount of carbon nanotubes produced. Results showed that by using the aerosol-assisted single furnace CVD method, rambutan-like structure of carbon nanotubes were successfully synthesized at various deposition temperatures ranging from 600-800°C with increment of 50°C. FESEM image showed the CNTs produced have smallest diameter with uniformed distribution at temperature of 700°C. The microraman spectra study further supported these results which showed the presence of single wall and multi wall CNTs with highest crystallinity and purity of CNTs with average diameter of -26.10 nm within the bundles. It also had the highest amount of carbon distribution as shown by the EDX analysis which is 77.32 at% of carbon and the lowest Id/Ig ratio of 0.69 representing good quality and high crystallinity of CNTs. Morever, by using the aerosol-assisted double furnace CVD method, single walled and multi walled carbon nanotubes were successfully synthesized at various deposition temperature ranging from 700-900°C. FESEM image showed that CNTs produced have smallest diameter with uniformed distribution at temperature of 800°C.The microraman spectra study further supported these results which showed the presence of single walled and multi walled CNTs and also presence of spiral-like structure of CNTs with highest crystallinity and purity at optimized deposition temperature of 800°C with average diameter of -8.06 nm within the bundles. It also had the highest amount of carbon distribution as shown by the EDX analysis and the lowest Id/Ig ratio of 0.54 representing good quality and high crystallinity of CNTs. It can be concluded that the best CNTs were produced by the aerosol-assisted double furnace CVD method as it has the smallest diameter and highest carbon distribution which shows better quality CNTs.